Free smoking cessation mobile apps available in Australia: a quality review and content analysis - Louise Thornton; Catherine Quinn; Louise Birrell; Ashleigh Guillaumier; Brad Shaw; Erin Forbes; Mark Deady; Frances Kay‐Lambkin (Elsevier, 2017)
Abstract Objectives: This review aimed to identify free, high‐quality, smoking cessation mobile applications (apps) that adhere to Australian smoking cessation treatment guidelines. Methods: A systematic search of smoking cessation apps was conducted using Google. The technical quality of relevant apps was rated using the Mobile Application Rating Scale. The content of apps identified as high quality was assessed for adherence to smoking cessation treatment guidelines. Results: 112 relevant apps were identified. The majority were of poor technical quality and only six 'high‐quality' apps were identified. These apps adhered to Australian treatment guidelines in part. The efficacy of two apps had been previously evaluated. Conclusions: In lieu of more substantial research in this area, it is suggested that the high‐quality apps identified in this review may be more likely than other available apps to encourage smoking cessation. Implications for public health: Smoking cessation apps have the potential to address many barriers that prevent smoking cessation support being provided; however few high‐quality smoking cessation apps are currently available in Australia, very few have been evaluated and the app market is extremely volatile. More research to evaluate smoking cessation apps, and sustained funding for evidence‐based apps, is needed.